A new nucleotide variant G1358A potentially change growth differentiation factor 9 profile that may affect the reproduction performance of Friesian Holstein cattle - Afifi Inayah; Sri Rahayu; Nashi Widodo; Widya Ayu Prasdini (Asian Pacific Journal of Reproduction, 2016)
Objective: To determine the polymorphism of GDF-9 gene in FH cattle that may affect its interaction with the BMP-15 protein. Method: Blood was taken from the jugular vein using 10 mL sterile syringes from ten Friesian Holstein cattle. The DNA were isolated from the whole blood and used as a template to amplify GDF-9 gene. The Amplicon (PCR product) was sequenced to identify the new SNP. The three-dimensional structure of GDF-9 protein was modeled by SWISS-MODEL. The characteristic of the protein structure was analyzed by using projectHOPE. The binding affinity GDF-9 into MBP was examined by PatchDock and FireDock. Results: The result indicates a new variant G1358A changed amino acid residue at position 435 from Arginine into Histidine (R453H). In silico analysis using projectHOPE predicted that the variant altered side chain of GDF-9 and changed its interaction with BMP-15. Further study suggested that the polymorphism R453H also reduce the binding affinity of the GDF-9 into BMP-15 from −85.58 kcal/mol (R453) into −80.79 kcal/mol (H453). Conclusion: The new variant G1358A at an estrous FH a cattle has potency alter GDF-9 profile that may affect to reproduction performance.